Analisis Perilaku konsumen Nano Store pada Masa Pandemi Covid-19 (Studi Kasus Pada Konsumen Nano Store di Kabupaten Subang, Indonesia) - Ramadhan, Nur (International Journal Administration, Business & Organization, 2021)
The Corona virus has become a pandemic outbreak that has spread throughout the world since December 2019. This pandemic has affected all aspects of human life from social to economic stability. One type of business that has been affected by the pandemic is a nano store. One of the things the authors highlight is the behavior of nano store consumers during the Covid-19 pandemic. The author conducted research on a of consumers in Subang Regency. The stages of consumer behavior include problem recognition, evaluating alternatives, purchasing decisions, and post-purchase evaluation. This research was conducted by distributing questionnaires to 100 respondents. Data processing from respondents' answers was carried out with a quantitative approach using the SPSS version 24 application with descriptive statistical analysis, the result was to know the mean and standard deviation. The results of the study indicate that consumer behavior is still classified as rational (good criteria) because it puts forward needs, quality, and adjusts to purchasing power.